Effects of nano silver on growth of Chrysanthemum morifolium in microponic system - Tùng, Hoàng Thanh; Huy, Nguyễn Phúc; Nam, Nguyễn Bá; Luận, Vũ Quốc; Hiền, Vũ Thị; Phượng, Trương Thị Bích; Nhựt, Dương Tấn (Vietnam Journal of Biotechnology, 2016)
Nano Silver has been proven to be effectively applied in the field of biotechnology. In the area of ​​plant biotechnology, nanoparticles have positive and negative effect on the growth of plants. The impact of nanoparticles on plant depends on the composition, content, size, chemical and physical propreties of nanoparticles as well as the plant species. The impact of silver nanoparticles on the problem of infection during culturing, the growth of plants in microponic systems and acclimatization of the plant in greenhouse were studied. In this work, the microponic medium supplemented with of 7.5 ppm silver nanoparticles showed the highest growth rate of Chrysanthemum after 2 weeks in culture. Results of qualitative and quantitative microbial content in microponic culture medium by 4 testing methods including Bergey’s Manual of Determinative Bacteriology, ISO 16266, ISO 21527-1 for bacteria and NHS-F15 for fulgi also showed that concentration of 7.5 ppm nanoparticles reduces the microbial content of the 8 species of bacteria (Corynebacterium sp., Enterobacter sp., Arthrobacter sp., Agrobacterium sp., Xanthomonas sp., Pseudomonas sp., Bacillus sp. and Micrococcus sp.) and three species of fungi (Aspergillus sp., Fusarium sp. and Alterneria sp.). The growth of Chrysanthemum plant in a concentration of nanoparticles is better than the other levels after 4 weeks in the greenhouse such as high survival rate (100%), plant height (13.3 cm), number of leaves per plant (14.67 leaves), number of roots per plant (26.67 roots), leaf length (4.03 cm), leaf width (3.77 cm), fresh weight (3816 mg) and dry weight (216 mg).